2006
DOI: 10.1111/j.1528-1167.2006.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Open‐field Behaviors and Water‐maze Learning in the F Substrain of Ihara Epileptic Rats

Abstract: Summary:Purpose: Genetically epileptic model rats, Ihara epileptic rat (IER/F substrain), have neuropathologic abnormalities and develop generalized convulsive seizures when they reach the age of ∼5 months. Because the neuromorphologic abnormalities are centered in the hippocampus, we expected to observe spatial cognitive deficits. The present study aimed to evaluate emotionality and learning ability of the F substrain of IER.Methods: To determine whether deficits are caused by inborn neuropathologic abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…More specifically, increases in the number of crossed squares, vertical stands, entering the center and the duration of the time spent in the center are the signs of increased locomotor activity and decreased fear (5,13) . Grooming is an important and evolutionarily ancient behavior.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, increases in the number of crossed squares, vertical stands, entering the center and the duration of the time spent in the center are the signs of increased locomotor activity and decreased fear (5,13) . Grooming is an important and evolutionarily ancient behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency and the degree of seizures increase with aging (Additional file 1: Video 1) [3,4] Neuropathological investigation revealed that IERs exhibit small neuronal disarrangements consisting of irregular arrangements of pyramidal cells, gap formation in the array of the pyramidal cell layer, and abnormal tiny loci of neuronal clusters in the hippocampal formation (i.e., microdysgenesis; MDG) [5]. In addition, IERs exhibit behavioral impairment in social interaction, controlling emotions and spatial learning even before the onset of any seizure-related behaviors [6]. Similarly, some cases of human epilepsy are often accompanied by such psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that it is possible to treat epilepsy using pharmacological substances, about 30-40% of the patients are resistant to such treatment (WHO, media Center 2016). In addition, a long-term consumption of the drugs negatively affects the patients' cognitive functions [1][2][3]. The effectiveness of pharmacological agents, used for epilepsy treatment is limited due to incomplete understanding of the mechanisms involved in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%